Coeval fluctuations of the Greenland ice sheet and a local glacier, central East Greenland, during late glacial and early Holocene time - Levy, Laura B.; Kelly, Meredith A.; Lowell, Thomas V.; Hall, Brenda L.; Howley, Jennifer A.; Smith, Colby A. (Geophysical Research Letters, 2016)
We present a 10 Be chronology of late glacial to early Holocene fluctuations of a Greenland ice sheet outlet glacier and the adjacent Milne Land ice cap in central East Greenland. Ages of boulders on bedrock indicate that both ice masses receded during the Younger Dryas (YD), likely due to rising summer temperatures. Since Greenland ice core records register cold mean annual temperatures throughout the YD, these ice-marginal data support climate conditions characterized by strong seasonality. The ice sheet outlet glacier and ice cap deposited inner Milne Land Stade moraines at 11.4 ± 0.8 ka and 11.4 ± 0.6 ka, respectively (mean moraine ages and 1σ uncertainties). Based on the coeval moraine ages, we suggest that both ice masses responded to climate conditions acting on the ice margins, specifically ablation. Moreover, the ice sheet responded sensitively (i.e., on the same time scale as a small ice cap) to climate conditions.